The Stories of Three EFL College Students in East Java Universities amid the Covid-19: EFL Online Learning Process - Haris Sugianto; Abdul Aziz (Scope : Journal of English Language Teaching, 2023)
The Covid-19 pandemic has also been felt by the world of education, especially in Indonesia. All parties involved in schooling are unprepared to handle this rapid outbreak. Distance learning in the network (online) is a new thing for both teachers and students themselves. Through the use of online applications, university lecturers in Indonesia continue to carry out their teaching duties by interacting online with students. The interactions are by uploading lecture material into the online application, giving assignments, online discussions, and reviewing the learning process. This research presents the results of an interview study with three English language education students from university in Indonesia about how their perceptions of their online learning experiences during the Covid-19 pandemic. This research presented as an inquiry case study that looks at how participants position themselves in connection to the phenomena. The results of this research show that online learning carried out in an effort to prevent the spread of Covid-19 is good to do as an alternative during social distancing. The Covid-19 outbreak makes us have to limit social interaction to break the chain of transmission. In addition to the learning process and maintaining the interaction between lectures and students, online learning is a good idea because it gives students new knowledge and experience about technology, particularly online learning applications. Technology has been crucial in the teaching of English since it makes the creation and the use of electronic learning tools considerably simpler where students can get to know various online applications and how to use them. However, there are some issues that need to receive special attention, such as the instability of the internet network and economic factors. The result of this research will become as an input11 for lecturers and institutions in carrying out this online learning process so that it continues to run optimally.